Analisis Penanganan Limbah Konstruksi pada Proyek Pasar Tumburuni di Kabupaten Fakfak: Analysis of Construction Waste Handling at the Tamburuni Market Project in Fakfak Regency - Jusmawandi, Jusmawandi; Putra, Herdy Pratama (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Construction waste is a threat to the community environment and living creatures around construction projects. It is necessary to handle construction waste appropriately considering that not all materials can be used 100% during the construction process. Construction waste causes hazardous chemical contamination which is the result of a number of hazardous chemicals being applied to building materials, or the discharge of chemicals in the construction and demolition waste stream. This research aims to apply the 3R principle (Reduse, Reuse and Recycle) contained in the Responsible Waste Management Hierarchy structure. Case study of the Tuumburuni Market development project in Fakfak Regency. Tumburuni Market is the first modern market built in Fakfak Regency and has become a role model for other construction projects. Good waste management in the construction process will reduce the impact on the environment. The research method uses survey and interview methods. The data obtained is explained in data tabulation and described based on the Waste Management Hierarchy theory. Research results show that as many as 80% of consumable materials go through a reuse process before finally being thrown away. Meanwhile, 20% of wood waste is not used because it is broken and unfit for use.